2021
DOI: 10.1136/postgradmedj-2020-139512
|View full text |Cite
|
Sign up to set email alerts
|

What do beta-lactams add to vancomycin or daptomycin in the treatment of patients with methicillin-resistantStaphylococcus aureusbacteraemia? A review

Abstract: Several studies have documented the synergy between vancomycin/daptomycin and various beta-lactams, and clinical studies have studied this combination therapy in humans. We review the published literature on this topic to know the utility of the combined treatment with beta-lactams in treating bacteraemia methicillin-resistant Staphylococcus aureus (MRSA) infections. Fifteen observational studies, three randomised clinical trials and three systematics reviews are analysed in this article. Observational studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…1g ; ∑FIC min = 0.6). Ceftobiprole-vancomycin synergy has previously been observed ( 39 ), and several clinical studies of β-lactam combinations with vancomycin have been reported and recently reviewed ( 40 ). Floxuridine, which demonstrated strong synergy with cefoxitin in a prior study ( 37 ), demonstrated effectively no synergy with ceftobiprole ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1g ; ∑FIC min = 0.6). Ceftobiprole-vancomycin synergy has previously been observed ( 39 ), and several clinical studies of β-lactam combinations with vancomycin have been reported and recently reviewed ( 40 ). Floxuridine, which demonstrated strong synergy with cefoxitin in a prior study ( 37 ), demonstrated effectively no synergy with ceftobiprole ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Combination therapy with vancomycin plus beta-lactams for MRSA bacteremia showed lower clinical failure rates, and the combination exposures significantly suppresses the development of VISA [ 28 , 29 ]. Several studies have documented that adding a beta-lactam to vancomycin or daptomycin may help shorten bacteremia and avoid recurrences in patients with MRSA bacteremia [ 30 ]. Daptomycin is not routinely used in neonates because of a scarcity of literature on its efficacy and safety in infants.…”
Section: Discussionmentioning
confidence: 99%